PEMANFAATAN EKSTRAK BUAH SALAK (Salacca zalacca (Gaertn.) Voss) SEBAGAI ANTI-AGING ALAMI DALAM SEDIAAN BODY SCRUB - Dara, Riza Permata; Maimunah, Siti; Prayoga, Andre (Herbal Medicine Journal, 2024)
This study was aimed at formulating Salak fruit extract in a cream formulation and testing its anti-aging eﬀectiveness. Flavonoid compounds in salak fruit are efficacious as antioxidants that are able to neutralize free radicals so they can improve signs of aging on the skin such as dry skin and enlarged pores and wrinkles. This research was conducted at the Pharmaceutical Chemistry Laboratory of Sari Mutiara Indonesia University in June-August 2023. The tools used were skin analyzer and moisture checker. Salak fruit samples were obtained from the Sihopur village Tapanuli Selatan regency, North Sumatra. The irritation test of three volunteers used salak extract cream with the highest concentration of 7%. The anti-aging activity test used 15 volunteers. Parameters measured include moisture content, number of pores and wrinkles. Statistical data was analyzed using the SPSS method. The results show that the ethanol extract of Salak fruit leaves can be formulated in a homogeneous type A / M cream dosage form, with a pH of 6,3-5,2, a viscosity of 19.000-47.000 cps, non-irritating and stable in storage for 12 weeks. The results of the analysis with the skin analyzer showed that the skin condition changed for the better, namely increased water content 32,3%, reduced pores 10,4% and wrinkles 13,2%. Cream preparations with a concentration of 7% show the best anti-aging eﬀectiveness.